2021
DOI: 10.17576/jskm-2021-1901-06
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Lay Knowledge of Autism Spectrum Disorder in Malaysia

Abstract: Today, increasingly more people worldwide are aware about Autism Spectrum Disorder (ASD). However, their actual understanding about ASD is yet unknown. In this study, the lay knowledge on the social communication and language deficits of ASD was investigated using a brief survey involving an elite sample in Malaysia. The survey findings revealed that the vast majority of the respondents had superficial understanding about the social communication and language deficits of ASD. In general, they could relate to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Additionally, this study found a lower rate of psychiatric comorbidity compared to other studies previously done. Possible reasons include the low levels of mental health literacy and stigmatizing attitudes towards mental health problems among the public in Malaysia ( 59 , 60 ). The stigma associated with psychiatric and neurodevelopmental disorders may possibly compel individuals to refrain from labeling their afflicted family members with disorders and under-reporting the severity of behavioural issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this study found a lower rate of psychiatric comorbidity compared to other studies previously done. Possible reasons include the low levels of mental health literacy and stigmatizing attitudes towards mental health problems among the public in Malaysia ( 59 , 60 ). The stigma associated with psychiatric and neurodevelopmental disorders may possibly compel individuals to refrain from labeling their afflicted family members with disorders and under-reporting the severity of behavioural issues.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence we found was lower compared to other studies (ranging from 72 to 93.7%) in children with ASD ( 4 , 6 , 63 ). This difference may be due to higher stigma and limited awareness about ASD and mental illness in Malaysia ( 59 , 60 , 64 ), causing caregivers to report fewer symptoms their child might be having.…”
Section: Discussionmentioning
confidence: 99%
“…Antara topik perbincangan yang popular seperti pengalaman penginapan dikalangan keluarga dengan anak mempunyai autisme (Freund et al, 2019), peranan percutian terhadap kualiti hidup keluarga kanak-kanak mempunyai autisme (Mactavish et al, 2007), manfaat aktiviti pelancongan sebagai salah satu elemen terapi carakerja autisme (Sarol & Çimen, 2015;Bumin et al, 2015), penglibatan kanak-kanak mempunyai autisme dalam aktiviti rekreasi dan riadah (Solish et al, 2010;Potvin et al, 2013;Stacey et al, 2018), pengalaman ibu bapa ketika melancong bersama kanak-kanak mempunyai autisme (Sedgley et al, 2017;Amet, 2013), dan suara ibu bapa untuk beriadah (Kim et al, 2018). Namun, populariti kajian berkaitan autisme di Malaysia sehingga kini dilihat masih berada di peringkat memupuk kesedaran tentang autisme yang lebih memfokuskan kepada pengenalan awal autisme (Xiang Neik et al, 2014;Lim, 2015;Mohd Kassim & Mohamed, 2019) dan penilaian kesedaran masyarakat tentang autisme (Mohd Salleh et al, 2018;Hui et al, 2021), cabaran ibu bapa membesarkan anak mempunyai autisme (Chu et al, 2018) dan suasana tempat pembelajaran autisme (Zulkanain & Mydin, 2019).…”
Section: Pengenalanunclassified